Property Investment and Rental Rate under Housing Price Uncertainty: A Real Options Approach - Honglin Wang; Fan Yu; Yinggang Zhou (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2018)
The conventional wisdom that housing prices are the present value of future rents ignores the fact that unlike dividends on stocks, rent is not discretionary. Housing price uncertainty can affect household property investments, which in turn affect rent. By extending the theory of investment under uncertainty, we model the renter's decision to buy a house and the landlord's decision to sell as the exercising of real options of waiting and examine real options effects on rent. Using data from Hong Kong and mainland China, we find a significant effect of housing price on rent and draw important policy implications.
Keywords: C00; 330